The Efficacy and Safety of Brolucizumab for the Treatment of nAMD: A Systematic Review and Meta-Analysis - Chuan, Junlan; Liu, Lianqiao; Feng, Yumei; Wang, Mengdan; Li, Gang; Lv, Qin (Frontiers in Pharmacology, 2022)
Introduction: As demonstrated in pivotal clinical trials, brolucizumab can be used to treat neovascular age-related macular degeneration (nAMD) because it antagonizes vascular endothelial growth factor (VEGF) in the vitreous. However, brolucizumab may cause retinal vasculitis obliterans in the presence of inflammation in the eyes. In the present study, a meta-analysis of randomized controlled trials (RCTs) was conducted to evaluate the efficacy and safety of brolucizumab. Methods:ClinicTrail.gov., Embase, Cochrane Library, and PubMed were retrieved from inception until 31 December 2021 for RCTs assessing the efficacy and safety of brolucizumab. Changes in best corrected visual acuity (BCVA) and central sub-field thickness (CSFT) and incidence of adverse events, serious adverse events, and serious ocular adverse events were extracted from eligible RCTs. A meta-analysis was performed using RevMan 5.4.1. Results: A total of six RCTs with 3,574 participants were finally involved in this meta-analysis. The changes of best corrected visual acuity (BCVA) showed no statistically significant difference between the brolucizumab-treated group and aflibercept-treated group. Brolucizumab induced higher central sub-field thickness (CSFT) reduction than the control agent (aflibercept). The incidence of adverse events was similar between the brolucizumab group and control group (OR 0.63, 95% CI 0.37 to 1.08, p = 0.09), and brolucizumab caused fewer serious adverse events (OR 0.78, 95% CI 0.63 to 0.95, p = 0.01). However, brolucizumab could lead to more serious ocular adverse events than Lucentis and aflibercept (OR 2.15, 95% CI 1.11 to 4.16, p = 0.02). Conclusion: Brolucizumab was non-inferior to other anti-VEGF agents in improving BCVA and decreasing CSFT. But it caused more serious ocular adverse events which is worthy of special attention by ophthalmologists.